IMPROVING STUDENTS’ SPEAKING ABILITY BY SHORT DILAOGUES MEMORIZATION - Atrianus Toni (Edumedia : Jurnal Keguruan dan Ilmu Pendidikan, 2022)
This research aimed at improving students’ speaking ability using short dialogue. It was a classroom action research (CAR). The study was conducted in a cyclic process starting from planning, acting, observing, and reflecting. What technique? Technique was implemented in two cycles. The subjects of this research were elementary level students from SMAS Panca Setya Sintang. The study found out that the implementation of short dialogue memorization technique has improved the students' speaking ability. The students also improved their active involvement in class. In the first cycle, only some students participated in class actively, but most of them were very active in the second cycle. Based on the students’ score data, more than half of the students got higher in each aspect. Compared with the data from Cycle I, Cycle II was dominated by the students who got a score of 6 in each aspect, while Cycle I was dominated by the students who got score 2 and 1. Almost all students passed the criteria of success, 70. Therefore, the teachers were recommended to improve the students’ speaking ability using short dialogue memorization technique.